The Influence of Workload and Job Stress on the Performance of Online Motorcycle Taxi Drivers (Grab, Maxim, and Gojek) in the Semarang City Area - Purnomo, Ardiansyach Maulana; Waluyo, Dwi Eko (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to analyze the influence of workload and job stress on employee performance among online motorcycle taxi drivers (Grab, Maxim, and Gojek) in the Semarang City area. The population in this research consists of online motorcycle taxi drivers (Grab, Maxim, and Gojek) in the Semarang City area, with a sample size of 96 respondents, who meet the criteria of having worked for a minimum of one year. This research found that the workload variable has a significant negative partial effect on the employee performance of online motorcycle taxi drivers (Grab, Maxim, and Gojek) in the Semarang City area, and the job stress variable also has a significant negative partial effect on the decline in employee performance among online motorcycle taxi drivers (Grab, Maxim, and Gojek) in the Semarang City area.